2018
DOI: 10.2196/mhealth.9494
|View full text |Cite
|
Sign up to set email alerts
|

Preferences of Underserved Chilean Women on a Mobile Technology Intervention for Cervical Cancer Screening: Qualitative Study

Abstract: Background. In Chile and Latin America, cervical cancer disproportionately affects women of low socioeconomic status. Mobile technology (mHealth) may be able to address this disparity by targeting women in underserved populations. However, there is a lack of information regarding barriers to the implementation of mHealth interventions in underserved populations.Methods. We conducted nine focus groups among women 25-64 years of age to better understand the implementation barriers and perceptions of a text messa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 16 publications
1
18
0
6
Order By: Relevance
“…In our study, both women and health authorities were against receiving results via SMS, mainly because they considered that this type of news must be provided in a face-to-face health consultation so that the patients are able to ask questions and get rid of their doubts. The women's rejection of receiving results by SMS was also mentioned in a study conducted in Chile, which found that Chilean women expressed concerns regarding the impersonal nature of the communication by SMS to communicate medical results [33]. Similarly, a colorectal cancer screening study in the United States found that patients did not want to receive results via SMS [57], particularly as it was not an appropriate communication mode to receive what they considered to be bad news.…”
Section: Principal Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, both women and health authorities were against receiving results via SMS, mainly because they considered that this type of news must be provided in a face-to-face health consultation so that the patients are able to ask questions and get rid of their doubts. The women's rejection of receiving results by SMS was also mentioned in a study conducted in Chile, which found that Chilean women expressed concerns regarding the impersonal nature of the communication by SMS to communicate medical results [33]. Similarly, a colorectal cancer screening study in the United States found that patients did not want to receive results via SMS [57], particularly as it was not an appropriate communication mode to receive what they considered to be bad news.…”
Section: Principal Findingsmentioning
confidence: 99%
“…In addition, it is important to use keywords to make the content clear without upsetting the recipient [30][31][32]. A study conducted in Chile about the SMS preferences of underscreened women showed that clarity and simplicity of the received message were very important for them [33]. The legitimacy of the sender and privacy issues, such as disclosing a result to a third person in shared cell phones, have also been shown to be relevant topics on SMS content [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…Dalam melakukan deteksi Dini pada kanker serviks pada wanita usia subur dapat dilakukan dengan pendekatan mengunakan via telepon dan SMS dimana wanita menerima telepon dan sms dengan Waatshap Sebagai salah satu pengingat untuk melakukan pemeriksaan ke Puskesmas. Dan tenaga kesehatan atau bidan dapat mengingatkan untuk melakukan kunjungan ke tenaga kesehatan untuk ke pelayanan kesehatan yang terdekat kesehatan (Soto et al, 2018).…”
Section: Strategi Dalam Melakukan Skrining Kanker Serviks a Menggunakan Media Elektronikunclassified
“…Hambatan yang kedua masalah ekonomi yang masih rendah karena sebagian besar wanita mempunyai masalah ekonomi yang rendah untuk melakukan deteksi dini ataupun pemeriksaan ke pelayanan kesehatan (Soto et al, 2018). Untuk melakukan deteksi dini pada wanita masih banyak yang kahawatir dan takut pada efek samping terjadi ketika setelah melakukan pemeriksaan di pelayanan kesehatan (Ragan et al, 2018).…”
Section: Melakukan Kunjunganunclassified
See 1 more Smart Citation